Rapamycin inhibits clonal expansion and adipogenic differentiation of 3T3-L1 cells. - Wen‐Chen Yeh; Barbara E. Bierer; Steven L. McKnight (1995)
Differentiating 3T3-L1 cells express an immunophilin early during the adipocyte conversion program as described in this issue [Yeh, W.-C., Li, T.-K., Bierer, B. E. & McKnight, S. L. (1995) Proc. Natl. Acad. Sci. USA 92, 11081-11085]. The temporal expression profile of this protein, designated FK506-binding protein (FKBP) 51, is concordant with the clonal-expansion period undertaken by 3T3-L1 cells after exposure to adipogenic hormones. Having observed FKBP51 synthesis early during adipogenesis, we tested the effects of three immunosuppressive drugs--cyclosporin A, FK506, and rapamycin--on the terminal-differentiation process. Adipocyte conversion was not affected by either cyclosporin A or FK506 and yet was significantly reduced by rapamycin at drug concentrations as low as 10 nM. Clonal expansion was impeded in drug-treated cultures, as was the accumulation of cytoplasmic lipid droplets normally seen late during differentiation. Rapamycin treatment likewise inhibited the expression of CCAAT/enhancer binding protein alpha, a transcription factor required for 3T3-L1 cell differentiation. All three of these effects were reversed by high FK506 concentrations, indicating that the operative inhibitory event was mediated by an immunophilin-rapamycin complex.